Collection, cryostorage, transplantation, and disposal of hematopoietic stem cell products - Kriegsmann, Katharina; Schmitt, Anita; Kriegsmann, Mark; Bruckner, Thomas; Müller-Tidow, Carsten; Wuchter, Patrick (Biology of blood and marrow transplantation, 2019)
Many transplantation centers routinely collect 1 or more autologous peripheral blood stem cell (PBSC) grafts in patients with hemato-oncologic and autoimmune disorders. However, subsequent high-dose chemotherapy and autologous blood stem cell transplantation (ABSCT) are often not performed, for various reasons. Currently, little is known about the actual utilization rate of stored PBSCs. We retrospectively analyzed the collection, storage, and disposal practices of PBSC products from a large cohort of patients (n=1020) with hematologic, oncologic, and autoimmune disorders at our institution over a 12-year period. Patients with multiple myeloma were excluded. Based on our institution-specific charges, we estimated the costs for PBSC collection/processing and storage. The median number of sufficient PBSC collections per patient in the whole cohort was 2 (range, 1 to 6). We could demonstrate that only 67% of all patients who had collected sufficient PBSCs for transplantation actually underwent ABSCT, and only a small minority of all patients (4%) underwent multiple ABSCTs. The actual use of the stored PBSC grafts varied among disease entities from >80% to 0%. From a retrospective standpoint, the collected and discarded (definitively not used) or stored (potentially not used) cryostored PBSCs were associated with considerable costs of collection, cryopreservation, and long-term cryostorage. Although keeping open the therapeutic option for future transplantations may be important, there is currently a huge discrepancy between collection/storage practices and actual utilization of the cryopreserved PBSCs, at a considerable cost and strain on patients. Our study provides a rationale for reevaluating the present standards.